The Haitian play: C. L. R. James' Toussaint Louverture (1936). (1st May 2011) - Sweeney, Fionnghuala
The play Toussaint Louverture, staged in London in 1936, was the first in a series of interventions by C. L. R. James into the representative politics and historical implications of the Haitian revolution. The theme was most famously to recur in The Black Jacobins (first published in 1938), a text whose shifting frames of reference and lines of emplotment have become central to contemporary discussions of the current postcolonial moment (Scott 2004). Despite the attention accorded Jacobins, the play has received little critical notice, largely because of the absence of a script authenticated as that originally performed in 1936, but never copyrighted or published. Using a range of archive evidence, this article argues that a document held in the Moorland-Spingarn Research Center, is, first, a copy of the text that formed the basis of the performance; and, second, a document whose circulation helps position James within the complex network of activity that constituted the black Atlantic response to the political and cultural opportunities of the early twentieth century. It considers the critical reception of the play, the significance of the London metropolitan setting, and the ways in which the plot may have been designed to anticipate, and play to, an audience self-image rooted in ambivalence to its own past, yet drawn to increasing possibilities of the politically and aesthetically new.